2017
DOI: 10.1016/j.biomaterials.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Novel lipoproteoplex delivers Keap1 siRNA based gene therapy to accelerate diabetic wound healing

Abstract: Therapeutics utilizing siRNA are currently limited by the availability of safe and effective delivery systems. Cutaneous diseases, specifically ones with significant genetic components are ideal candidates for topical siRNA based therapy but the anatomical structure of skin presents a considerable hurdle. Here, we optimized a novel liposome and protein hybrid nanoparticle delivery system for the topical treatment of diabetic wounds with severe oxidative stress. We utilized a cationic lipid nanoparticle (CLN) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(85 citation statements)
references
References 52 publications
(64 reference statements)
2
76
0
Order By: Relevance
“…Previous studies demonstrated that impaired or delayed healing was serious problem in some metabolic diseases including DM [6,8,9,10,11], because of several factors such as differentiation of the extracellular matrix dysfunction in fibroblasts and epidermal cells, and poor angiogenesis, e.g. [6,11].…”
Section: Histopathological Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies demonstrated that impaired or delayed healing was serious problem in some metabolic diseases including DM [6,8,9,10,11], because of several factors such as differentiation of the extracellular matrix dysfunction in fibroblasts and epidermal cells, and poor angiogenesis, e.g. [6,11].…”
Section: Histopathological Studymentioning
confidence: 99%
“…Most chronic wounds are associated with some illnesses including Diabetes mellitus (DM) [6][7][8] which is one of the most common disease worldwide [8,9]. In the United States, approximately 29.1 million people suffer from DM [10] and 15 % of patients with DM complain from serious complications such as chronic ulcers [8,10] which are characterized as impaired or non-healing wounds [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…7 However, the viral carriers are prone to immunogenicity and the risk of insertional mutagenesis. 8 Therefore, nonviral carriers have great potential in the application of gene therapy due to their better safety profile. gold NP, 10 and mesoporous silica, 11 have been developed to prepare antitumor nanomedicines with passive tumor-targeting properties due to the "enhanced permeability and retention" effect.…”
Section: Introductionmentioning
confidence: 99%
“…However, topical siRNA delivery remains challenging due to the unique structure of skin, with the stratum corneum proving difficult to penetrate, and endogenous RNAses degrading unpackaged siRNA. Cationic lipid nanoparticles have been used for both systemic as well as topical delivery, and in the present study, we utilized DOTAP and NaChol for creation of liposomes, which have shown promise in topical transdermal siRNA delivery in previous studies by our group and others . Although, liposomes are commonly used by many groups for siRNA delivery, the lipid ratios vary widely, and the optimal formulation remains unclear.…”
Section: Discussionmentioning
confidence: 98%
“…Evaluation of the release kinetics and penetration of the lipoplex/hydrogel vehicle was performed as previously described . Briefly, the dorsal skin of wild type C57 mice received a single application of lipoplex containing fluorescently tagged siGLO in hydrogel formulation, or an injection of lipoplex containing siGLO.…”
Section: Methodsmentioning
confidence: 99%